Treatment of temporal artery pseudoaneurysms. (August 2014) - Thomassen, Irene; Klompenhouwer, Elisabeth G; Willigendael, Edith M; Teijink, Joep AW
Purpose: To give an overview of the etiology and diagnostic process of superficial temporal artery pseudoaneurysms and to evaluate different treatment modalities. Basic methods: PubMed was used for searching multiple databases for relevant clinical studies. Principal findings: A total of 62 studies were included, harboring 82 patients. Surgical excision is the most frequently described treatment, but less invasive treatment modalities as coiling and thrombin injections are gaining popularity. Surgical treatment was successful in all cases (67/67). Endovascular treatment was successful in 69% (9/13); the five cases treated with thrombin injection were all successful. Complementary, a description of our experience with thrombin injection is given. Conclusions: Limited evidence of minimal invasive treatment for superficial temporal artery pseudoaneurysm is available. Based on this review combined with our limited experience, we suggest thrombin injections to be considered as the future primary treatment modality. In the case of unsuccessful exclusion of the aneurysm, surgical excision can be performed.